Are environmental risk factors for current wheeze in the International Study of Asthma and Allergies in Childhood (ISAAC) phase three due to reverse causation?. Issue 4 (23rd January 2019) - Silverwood, Richard J.; Rutter, Charlotte E.; Mitchell, Edwin A.; Asher, M. Innes; Garcia‐Marcos, Luis; Strachan, David P.; Pearce, Neil; ,
Abstract: Background: Phase Three of the International Study of Asthma and Allergies in Childhood (ISAAC) measured the global prevalence of symptoms of asthma in children. We undertook comprehensive analyses addressing risk factors for asthma symptoms in combination, at both the individual and the school level, to explore the potential role of reverse causation due to selective avoidance or confounding by indication. Objective: To explore the role of reverse causation in risk factors of asthma symptoms. Methods: We compared two sets of multilevel logistic regression analyses, using (a) individual level exposure data and (b) school level average exposure (ie prevalence), in two different age groups. In individual level analyses, reverse causation is a possible concern if individual level exposure statuses were changed as a result of asthma symptoms or diagnosis. School level analyses may suffer from ecologic confounding, but reverse causation is less of a concern because individual changes in exposure status as a result of asthma symptoms would only have a small effect on overall school exposure levels. Results: There were 131 924 children aged 6‐7 years (2428 schools, 25 countries) with complete exposure, outcome and confounder data. The strongest associations in individual level analyses (fully adjusted) were for current paracetamol use (odds ratio = 2.06; 95% confidence interval 1.97‐2.16), early life antibiotic use (1.65; 1.58‐1.73) and open fire cooking (1.44; 1.26‐1.65). In school level analyses, these risk factors again showed increased risks. There were 238 586 adolescents aged 13‐14 years (2072 schools, 42 countries) with complete exposure, outcome and confounder data. The strongest associations in individual level analyses (fully adjusted) were for current paracetamol use (1.80; 1.75‐1.86), cooking on an open fire (1.32; 1.22‐1.43) and maternal tobacco use (1.23; 1.18‐1.27). In school level analyses, these risk factors again showed increased risks. Conclusions & clinical relevance: These analyses strengthen the potentially causal interpretation of previously reported individual level findings, by providing evidence against reverse causation.